(untitled) (Brazilian Journal of Radiation Sciences, 2019)
Nuclear Power Plants (NPPs) based on Pressurized Water Reactors (PWRs) technology are considered an alternative to fossil fuels plants due to their reliability with low operational cost and low CO2 emissions. An example of PWR plant is Angra 2 built in Brazil. This NPP has a nominal electric power output of 1300 MW and made it possible for the country save its water resources during electricity generation from hydraulic plants, and improved Brazilian knowledge and technology in nuclear research area. Despite all these benefits, PWR plants generally have a relatively low thermal efficiency combined with a large amount of irreversibility generation or exergy destruction in their components, reducing their capacity to produce work. Because of that, it is important to assess such systems to understand how each component impacts on system efficiency. Based on that, the aim of this work is to evaluate Angra 2 by performing energy and exergy analyses to quantify the thermodynamic performance of this PWR plant and its components. The methodology consists in the development of a mathematical model in EES (Engineering Equation Solver) software based on thermodynamic states in addition to energy and exergy balance equations. According to the results, Angra 2 has energy efficiency of 36.18% and exergy efficiency of 49.24%. Reactor core is the most inefficient device in the NPP; it has exergy efficiency of 67.16% and is responsible for 63.88% of all exergy destroyed in Angra 2.